PERSUASIVE COMMUNICATION OF LIBRARIANS IN INCREASING VISITOR NUMBERS AND USER SATISFACTION AT THE BUNG HATTA PROCLAMATOR LIBRARY TECHNICAL IMPLEMENTATION UNIT IN BUKITTINGGI, WEST SUMATRA - Monojaya Simamora; Humaizi Humaizi; Maulana Andinata Dalimunthe (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study aims to analyze the persuasive communication of librarians on the increase in the number of visits and user satisfaction at the UPT Perpustakaan Proklamator Bung Hatta in Bukittinggi City. The theories used in this study are the Elaboration Likelihood Model by Petty and Cacioppo, the increase in the number of visits by Suwarno, and user satisfaction by Zeithaml et al. This study uses a correlational quantitative approach with a sample size of 400 people selected using accidental sampling techniques, and the population consists of all users of the UPT Perpustakaan Proklamator Bung Hatta in 2025. The data were analyzed using SmartPLS 4.1.1.6 software to test the direct effect of the variables. The research results show that there is a 68.8% effect of librarian persuasive communication on the increase in the number of visits, with a p-value of 0.000 < 0.05 and a t-statistic of 43.353. There is a 74.8% effect of librarian persuasive communication on user satisfaction, with a p-value of 0.000 < 0.05 and a t-statistic of 6.604. There is an effect of the increase in the number of visits on user satisfaction with a p-value of 0.000 < 0.05 and a t-statistic of 9.964. These findings prove that librarian persuasive communication has a positive effect on the increase in the number of visits and the satisfaction of users at the UPT Perpustakaan Proklamator Bung Hatta in Bukittinggi City.